Development of high‐sensitive enzyme immunoassays for gliadin quantification using the streptavidin‐biotin amplification system - Chirdo, Fernando Gabriel (1998)
Optimization of three enzyme immunoassays of very high sensitivity using three antiprolamin monoclonal antibodies (MAbs) (13B4, 11C4 and 12A1) is presented here. These MAbs are specific for those prolamins toxic for coeliac patients, as determined by immunoblotting analysis. Biotinylated MAbs were used in two of the assays. In a competitive ELISA, the binding of each biotinylated MAb to a gliadin‐coated solid phase was inhibited by gliadin in the fluid phase. The best result was obtained using the biotinylated MAbl3B4 (detection limit: 20 ng ml⁻¹). With regard to capture ELISA, we tested the performance of the three MAbs. In this sandwich ELISA, the MAb used for antigenic capture was the same as that used as secondary biotinylated antibody. The MAbl2Al had the best performance (detection limit: 1 ng ml⁻¹). The use of biotin‐labelled gliadin in a quantitative immunoassay with a detection limit of 5 ng ml⁻¹ is also reported. This assay involves an antigenic capture using the MAbl2Al followed by a competition between biotinylated and non-biotinylated gliadin. We have found the use of the streptavidin-biotin interaction as signal amplification system to be very useful. This technique, as far as we know, has not been previously reported for gliadin quantification.